Uma proposta de educação ambiental utilizando o lixo como tema interdisciplinar - Dacache, Fabiana Modesto (2004)
The environmental problem holds some political, economical, cultural, and social questions, not only ecological ones. The environmentalist movement is a historical movement which discusses issues, all of them involved with environmental concerns. To achieve behavioral changes in the society, in order to make people more conscious about environmental problems, environmental education is seen as the best strategy. Environmental education theory should not become another discipline inserted in the formal educational curriculum, but the environment should, as a transversal theme, permeate all disciplines trying to achieve an interdisciplinary status. It is so much so that interdisciplinary actions have been appoint as the main strategy to reach true real world knowledge within its whole complexity. Nevertheless, difficulties have been impeding the adoption of this practice. Capra (2003) defend that to obtain the sustentable society its necessary teacher the basics principles of ecology, which he calls ecological alphabet and this education must be did by projects. Among environmental themes, the garbage is one of the most worrisome. Thus, this work proposes a series of procedures which try an environmental education with interdisciplinary focus, to get the ecological alphabet, using garbage as generating theme. It also narrates a pilot experience accomplished in two schools in which elementary teaching classes were made more sensitive and discussed the question of the garbage in a more complex manner than the one it uses to be approached in schools. At the end of the work, it was possible to evaluate and conclude that the theme garbage provides an excellent interdisciplinary exercise, leading students to try to find solutions for questions related to garbage, using the different disciplines as tools, besides leading us to understand the basics principles of ecology